Hippodonta lange-bertalotii Van de Vijver, Mataloni & Vinocur sp.nov. and related small-celled Hippodonta taxa - Blanco, Saúl (2012)
Hippodonta lange-bertalotii Van de Vijver, Mataloni & Vinocur sp. nov. is described from Crater Lake, Deception Island (South Shetland Islands). Present paper reports a detailed morphological description of this species by means of light and scanning electron microscopy. The main diagnostic criteria include the rhombic outline of the valves, the comparatively narrow striae and the presence of two shortened striae delimiting the central area. The adscription of this new species to the genus Hippodonta and the differences with related taxa are briefl y discussed. Additionally, the morphological variability of the similar H. pseudacceptata is examined analyzing the valvar ultrastructure of different populations collected from Western Europe or published in the literature. Hippodonta pumila is presented as a heterotypic synonym of H. pseudacceptata.